Território e alimentação em Icapuí (CE): o festival gastronômico da lagosta e as identidades dos povos do mar - Gondim Neto, Leopoldo (2022)
The research deals with Food, Territory and Identity of the peoples of the sea. This work main objective is to understand how the Lobster Festival dynamizes the configuration of the territory and the conformation of the identity of the people of the sea in Icapuí, a municipality located in the state of Ceará, from the food culture. We’ll discuss the issue of food as a vital human need and, therefore, present at all times in human history, having a cultural value that can represent and characterize a people, a region, a place and, thus, mark identities. Also part of the discussion will be the question of how the constitution and configuration of territories, which represent, in addition to living and subsistence spaces, spaces of domination, power and coexistence, demonstrate that food is also an object of interest in Geography, with an evident relationship with the dynamics of transformations, whether spatial, cultural or socioeconomic, marking the issue of identities and the value of belonging. The study will end up at the Lobster Festival, a gastronomic event whose crustacean is the highlight of all the dishes offered to the public. The festival presents itself as a tourist attraction, of cultural and gastronomic expression in the municipality of Icapuí. From the methodological point of view, we adopted the qualitative-quantitative approach of an exploratory nature, seeking through different sources to obtain subjective and descriptive data, collected through records and direct contact between the researcher and the object of study. In this context, fishermen and other “people of the sea” are important subjects, if not the main responsible, for the success of lobster as a gastronomic dish and in the festival. In view of the dynamics (social, territorial, economic) presented by the event, the following guiding question arose for the research: what effects does the Lobster Festival have for the people of the Icapuí sea, considering the different perspectives, especially related to local development and the conformation of their identities, as peoples of the sea, based on food culture? We consider, as a hypothesis, that the consumption of lobster, as well as its importance in the elaboration of this festival, has a very significant role in the configuration of the territory and in the conformation of the identity of the people of the sea in Icapuí, Ceará.